On the Lorenz Systems for the Incompressible Flow Between Two Concentric Rotating Cylinders (Journal of Partial Differential Equations, 2010)
A spectral method is used to derive a series of equations for axisymmetric Couette-Taylor flow. A three-modes system, which is similar to the Lorenz systems, is obtained by a suitable three-modes truncation of the Navier-Stokes equations for the incompressible flow between two concentric rotating cylinders. The stability of the three-modes systems is discussed. Moreover, the existence of its attractor and the estimation of Hausdorff dimension are given.
Keywords: Couette-Taylor flow; attractor; Hausdorff dimension